2022
DOI: 10.1186/s41687-022-00416-3
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Japanese version of the Pediatric Quality of Life Inventory Infant Scales

Abstract: Background PedsQL Infant Scales (PedsQL-I) are used to assess parent-reported health-related quality of life for children younger than 2 years. We determined the feasibility, reliability, and validity of the Japanese version of the PedsQL-I. Methods A total of 183 participants (parents) with infants aged 1–30 months were recruited from 8 day care centers and one pediatric clinic. Participants completed the PedsQL-I (infants aged 1–18 months), the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Several studies have already evaluated reliability and validity of the transposition of different PedsQL™ Module. [30][31][32][33][34][35][36] Li et al reported the feasibility and the psychometric properties of the Chinese version of the PedsQL™ 3.0 Healthcare Satisfaction Generic Module. [33] Instead, Reinfjell et al recommended the Norwegian version of the Pediatric Quality of Life Inventory™ 4.0 (PedsQL) generic core scales for self-reports and proxy-reports for children in the age groups ranging from 13-15 years.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have already evaluated reliability and validity of the transposition of different PedsQL™ Module. [30][31][32][33][34][35][36] Li et al reported the feasibility and the psychometric properties of the Chinese version of the PedsQL™ 3.0 Healthcare Satisfaction Generic Module. [33] Instead, Reinfjell et al recommended the Norwegian version of the Pediatric Quality of Life Inventory™ 4.0 (PedsQL) generic core scales for self-reports and proxy-reports for children in the age groups ranging from 13-15 years.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, a special TC team was composed of chief physicians, supervisor nurses, nursing graduates, therapists, and psychologists at pediatric department. Secondly, scales of pediatric quality of life inventory version 4.0 (PedsQL™ 4.0) [17] assessment was conducted on the patients before discharge and then set up health files, formulated discharge plans, and handed out record books to the patients' parents to prompt them to record their children's daily health status. Finally, to promote contact between patients' parents and medical nursing workers, a network video technique was used to provide SVE advice and training 2 to 3 weeks following discharge.…”
Section: Mri Examinationmentioning
confidence: 99%